Snowball Throwing on Students’ Reading Comprehension - Jumerli Ariati; Eni Fauziah Harahap (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
The objective of the research was to find out whether there is the significantt effect on the students’ reading comprehension using snowball throwing. The method of the research was the experimental research design which was quasi experimental design. The population of the study was the first semester English Education Department students of Teacher Training Faculty IAIN Padangsidimpuan academic year 2018/2019, which consisted of 31 classes were 806 students both IAIN Padangsidimpuan and Baharuddin Boarding School center, then 2 classes as the sample. They were Room 11 as the experimental class taught by snowball throwing and 12 as control class taught by the conventional method that was usually used by the lecturer namely Step True False. The instruments of research were between 10 items for matching words to the definition and 10 reading multiple-choice test. The result of this research showed that t-test 0.07 was lower than t-table 2.02 in which t-test t-table. The hypothesis was rejected. In conclusion, it means that there was not a significant effect of applying snowball throwing on the students’ reading comprehension.